1996
DOI: 10.1002/(sici)1096-9861(19960325)367:1<70::aid-cne6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of thalamic input to the specification of cytoarchitectonic cortical fields in the primate: Effects of bilateral enucleation in the fetal monkey on the boundaries, dimensions, and gyrification of striate and extrastriate cortex

Abstract: Bilateral enucleation was performed at different fetal ages during corticogenesis, and the brains were prepared for histological examination. Early-enucleated fetuses (operated prior to embryonic day 77) showed morphological changes at the level of the thalamus and the cortex. In the thalamus, there was a loss of lamination and a decrease in size of the lateral geniculate nucleus. There was a decrease in the size of the inferior pulvinar, but there was no change in the lateral pulvinar. The border of striate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 49 publications
8
79
0
Order By: Relevance
“…However, a more recent study demonstrated a tight window of opportunity during which this is possible (Gaillard & Roger, 2000). In a study in which binocular enucleation was performed at mid-gestation in macaque monkeys, loss of retinofugal connections and subsequent thalamocortical projections was observed, which ultimately altered the fate of V1 by creating a hybrid visual cortex, probably through cell ⁄ cell interactions (Rakic et al 1991;Windrem & Finlay, 1991;Dehay et al 1996). Early thalamic ablation also leads to a reduction in areal and laminar size (Windrem & Finlay, 1991).…”
Section: Thalamic Controlsupporting
confidence: 70%
“…However, a more recent study demonstrated a tight window of opportunity during which this is possible (Gaillard & Roger, 2000). In a study in which binocular enucleation was performed at mid-gestation in macaque monkeys, loss of retinofugal connections and subsequent thalamocortical projections was observed, which ultimately altered the fate of V1 by creating a hybrid visual cortex, probably through cell ⁄ cell interactions (Rakic et al 1991;Windrem & Finlay, 1991;Dehay et al 1996). Early thalamic ablation also leads to a reduction in areal and laminar size (Windrem & Finlay, 1991).…”
Section: Thalamic Controlsupporting
confidence: 70%
“…Furthermore, mechanisms independent of thalamic innervation appear to initiate the formation of primary sensory areas. Additional evidence supports the view that intrinsic cortical mechanisms are operative at early stages of area specification: the cytoarchitectural differentiation of the primary visual cortex of primates (area 17), as well as the characteristic laminar pattern of monoamine receptors in this area, emerge in the absence of cues from the retina (33,34). Transplantation experiments in transgenic mice also suggest that layer IV neurons of S1 are molecularly committed as early as E14 to become a distinct subpopulation (35).…”
Section: Discussionmentioning
confidence: 97%
“…Using a common space based on gyral/sulcal folding patterns allowed us to compare patterns of responses across subjects' occipital cortices relative to their own gyral and sulcal landmarks and this technique has been shown to outperform linear and nonlinear volume-based registration methods at aligning functionally defined visual areas (Fischl et al 1999;Hinds et al 2008Hinds et al , 2009). However, it should be noted that cortical folding patterns may differ between early-blind and sighted subjects (Dehay et al 1989(Dehay et al , 1996.…”
Section: Bold Data Analysismentioning
confidence: 99%